Military Activity in The Ottoman Empire In the Reign of Sultan Bayezid II ( 1481-1512 ) - Youssef, Ilham (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Compared with his father, Sultan Mohammad the Conqueror , Sultan Bayezid II achieved little – in the military field- on the European front. However, strategically looked at, they were of great importance. He managed to annex both cities Kilia and Crimean. Doing this the black sea became an Ottoman lake. He got involved in a war against Venice, and captured some positions; that helped to advance in the eastern basin of the Mediterranean Sea, and in its western basin as well. on the eastern front failure was dominant. Mamluks' forces managed in defeating several Ottoman armies. His peaceful policies and his slackness in front of the Safavids led to the eruption of several hostile anti-Ottoman movements, and allowed more Safavids influence in Anatolia. Finally to Sultan Bayzid II virtue is attributed for modernizing sea and land forces. Relying on fire arms his son, sultan Selim I succeeded in scoring decisive victories against the Safavids and Mamluks